PERAN ANALISIS SEMIOTIK DALAM FILM THE SOCIAL DILEMMA DALAM TEORI “CMC” COMPUTER MEDIATED COMMUNICATION - Novan Andrianto; Hasan Ismail (Lembaga Pengembangan Kinerja Dosen, 2022)
The Social Dilemma is a documentary film that premiered on September 9, 2020. Directed by Jeff Orlowski, the documentary film The Social Dilemma tells about the negative impact of using social media on society. The purpose of this study is to get an overview of the guide in the film The Social Dilemma. The method used in this study is qualitative, namely analyzing the signs in the film using Charles Sanders Pierce's semiotic theory and Computer-Mediated Communication. The results of the study illustrate that The Social Dilemma contains many signs in it. Every scene in the film successfully explains how social media can have a negative impactif used excessively. With an analysis carried out using Charles Sanders Pierce's semiotic theory and Computer-Mediated Communication, the film The Social Dilemma is considered to have been well-packaged.